Relationships between Attachment Style and Depression Level among Undergraduate Students - Amalia Madihie 1; Azlan Bin Andika; Fiona anak Kunang; Diyana Syazana Binti Omar; Debra Bte Simar; Chan Wei Sian (Educational Guidance and Counseling Development Journal, 2018)
This study was conducted to identify the depression level of university student in Sarawak based on four types of attachment style. Therefore, undergraduate (UG) students from a university as sample for this study. Three hundred and sixty UG students were randomly chosen to be the respondents for this study since the population was 2200 UG students in a faculty. Questionnaire was employed in the study to collect required information or data. Questionnaire consists of three parts which are Section A: Demographic of respondents, Section B: Experience in Close Relationship Test (ECR), and Section C: Centre for Epidemiologic Studies Depression Scale (CES-D). ECR applied to determine the attachment style of students and CES-D used to identify the level of depression of students. As for the data analysis, Pearson Correlation Analysis was carried out.  Finding showed there was significant relationship between attachment style and depression level among the UG students where the p-value (0.000) is smaller than alpha value (0.005).  Expertise could utilize the findings of study to develop some suitable module of intervention to help client suffer from depression due to relationship problem.